CRM 1-Mediated Degradation and Agonist-Induced Down-Regulation of β-Adrenergic Receptor mRNAs - Bai, Ying (2006)
The β(1)-adrenergic receptor (β(1)-AR) mRNAs are post-transcriptionally regulated at the level of mRNA stability and undergo accelerated agonist-mediated degradation via interaction of its 3' untranslated region (UTR) with RNA binding proteins, including the HuR nuclear protein. In a previous report [Kirigiti et al. (2001). Mol. Pharmacol. 60:1308-1324), we examined the agonist-mediated down-regulation of the rat β(1)-AR mRNAs, endogenously expressed in the rat C6 cell line and ectopically expressed in transfectant hamster DDT(1)MF2 and rat L6 cells. In this report, we determined that isoproterenol treatment of neonatal rat cortical neurons, an important cell type expressing β(1)-ARs in the brain, results in significant decreases in β(1)-AR mRNA stability, while treatment with leptomycin B, an inhibitor of the nuclear export receptor CRM 1, results in significant increases in β(1)-AR mRNA stability and nuclear retention. UV-crosslinking/immunoprecipitation and glycerol gradient fractionation analyses indicate that the β(1)-AR 3' UTR recognize complexes composed of HuR and multiple proteins, including CRM 1. Cell-permeable peptides containing the leucine-rich nuclear export signal (NES) were used as inhibitors of CRM 1-mediated nuclear export. When DDT(1)MF2 transfectants were treated with isoproterenol and peptide inhibitors, only the co-addition of the NES inhibitor reversed the isoproterenol-induced reduction of β(1)-AR mRNA levels. Our results suggest that CRM 1-dependent NES-mediated mechanisms influence the degradation and agonist-mediated down-regulation of the β(1)-AR mRNAs.